Optimized Enoxolone-Loaded Microsponges for Drug Delivery: A Design of Experiments Approach - Juste Baranauskaite; Sedef Sefer; Augusta Zevzikoviene; Andrejus Zevzikovas; Liudas Ivanauskas (Pharmaceuticals)
Enoxolon is widely recognized for its pharmacological potential, exhibiting antioxidant, anti-inflammatory, anticancer, and antiviral properties. Objectives: This study aimed to develop an enhanced formulation of enoxolone-loaded microsponges as a novel drug delivery system. A design of experiments (DoE) approach was employed for the optimization process. Methods: The microsponges were produced using the quasi-emulsion technique. The selected formulation was evaluated for yield, particle size, and entrapment efficiency. Furthermore, the microsponges were incorporated into a 1% MC solution matrix, and in vitro release studies were performed to assess their drug delivery performance. Results: The optimal formulation was determined through the DoE methodology, which involved varying the concentrations of methylcellulose (MC) (0.55–1.87%, w/w), polyvinyl alcohol (PVA) (0.5–1%, w/w), and Tween 80 (TW80) (1.5–2.5%, w/w). The results showed a particle size of 142.8 ± 10.02 µm and an entrapment efficiency of 80.3 ± 1.99%. When comparing the optimized microsponge formulation to pure enoxolon, a 1.29 times higher release rate was observed (p ≤ 0.05). Conclusions: Following optimizationand physicochemical characterization studies were conducted to further assess the formulation. These findings suggest that microsponge-based delivery systems hold considerable potential as an alternative platform for the topical treatment of chronic periodontitis.